Al-Azhar University's Indonesian Student Alumni Strategic Role Analysis in Influencing the Politics of Indonesia-Egypt Foreign Policy - Arsyad Ihsanulhaq, Pangeran; Muttaqin, Mohammad Izdiyan (Riviera Publishing, 2024)
Al-Azhar University has a crucial role in shaping Indonesia's domestic politics and foreign policy, especially in its relations with Egypt. The university's Indonesian alums have significantly contributed to this process, occupying strategic positions in government and religious institutions. This research aims to analyze the impact of these alumni on Indonesia-Egypt diplomatic relations through their roles in policy formulation. This study employs a qualitative research method, utilizing a descriptive-analytical approach. Data was collected through secondary sources, including relevant documents and literature, and analyzed using qualitative analysis techniques. The results demonstrate that Indonesian alums of Al-Azhar University have substantially influenced Indonesia's foreign policy towards Egypt, particularly in promoting moderate Islamic values and diplomacy. Their involvement has strengthened bilateral relations, as evidenced by increased educational cooperation and diplomatic initiatives. The findings emphasize the strategic role of these alumni in bridging the diplomatic gap between Indonesia and Egypt through soft power diplomacy.